(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The article discusses the dramatic scenes in Jamal Kamal’s poetry as a result of polyphonic imagery, their unique poetic features, genesis, artistic appeal, richness of intellectual generalizations, social appeal and repercussions.